The Price of Digital Access: Conflicts of Centrality between Cultural Capital and ICT Capital among the Middle and Lower Classes of Bogotá, Colombia - Oliveros Fortiche, Diana Esperanza (2017)
Mastering digital technologies has become a necessary skill in the academic, workplace and social spheres. Being disconnected —not using technological communication devices or not having control over them— leads to situations of inequality of opportunities and social invisibility. The following text includes the theoretical framework formulated by Bourdieu and from there, it proposes the category of ICT Capital as an advance towards understanding issues related to digital access and its transforming social relationship. The most significant findings show how current individuals subordinate their cultural capital, forms of interaction, languages, consumption of cultural goods, symbolic and statutory legitimacy to the technological experience of the digital world.